An interactive video to demonstrate how to characterize nanoparticles - Rasteiro, Maria Graça (2014)
This work deals with the production of multimedia tools for distance learning. The course will be essentially based on hypermedia contents and can be delivered either in the e-learning or b-learning format. The option was to use interactive videos and, in this demonstration, a video used for the teaching of nanoparticles characterization using dynamic light scattering will be presented. This choice allows the student to choose his own strategy to learn about the measuring technique, since the video is prepared for interaction with the user. This feature is particularly important for lifelong learning courses dedicated to users already in the job market, for whom access to real laboratories can be more difficult and limited.